Intercultural communication : globalization and social justice - Sorrells, Kathryn (SAGE, 2016)
"This student introduction examines intercultural communication within the geopolitical, economic, and cultural context of globalization. It takes a social justice approach and provides a framework to create a more fair and equitable world through communication."
Terminologický slovník
Keywords: interkulturní komunikace; globalizace -- sociální aspekty; sociální spravedlnost; intercultural communication; globalization -- social aspects; social justice; učebnice; textbooks